Project evaluation and the depletion of natural capital: an application of the sustainability principle - von Amsberg, Joachim (World Bank WashingtonUS, 1993)
Summarizes the need for a sustainability constraint on economic activities and develops a methodology for reflecting a sustainability constraint in the economic anaysis of projects. Tries to show how conventional evaluation of natural capital depletion in cost-benefit analysis is deficient and how the deficiencies can be overcome.